Frequency domain analysis of steady-state visual evoked potentials in dogs with optic neuritis: a pilot study - Lee, Teck-Geun; Kim, Joon-Young (Frontiers in Veterinary Science, 2025)
Visual evoked potentials (VEP) are electrophysiological signals used to assess visual pathway function, with applications in diagnosing optic nerve disorders. This study compared the diagnostic utility of transient VEP (TVEP) and steady-state VEP (SSVEP) in dogs with optic neuritis, focusing on SSVEP’s frequency-domain advantages. Seven dogs with optic neuritis and seven controls matched for breed, age, and weight were evaluated. TVEP and SSVEP were recorded without anesthesia using standardized protocols, and parameters were analyzed in time and frequency domains. Significant reductions in SSVEP Frequency-Domain amplitude (FD amplitude), Time-Domain amplitude (TD amplitude), and Signal-to-Noise Ratio (SNR) were observed in the optic neuritis group (FD amplitude: p < 0.001, TD amplitude: p < 0.001, SNR: p < 0.001). TVEP N1-P2 amplitude was also significantly lower in the optic neuritis group (p < 0.001), while P2 latency showed no significant differences. Indirect comparisons revealed that TVEP amplitudes were larger, likely due to noise artifacts in time-domain analysis. SSVEP demonstrated superior noise resistance and minimized subjective interpretation. These results suggest SSVEP’s potential as a reliable, non-invasive diagnostic tool for optic neuritis in dogs, with further studies needed to confirm its broader applications in veterinary ophthalmology.